Implementation of Business Strategy, Technology Usage, and Business Continuity during the Covid-19 Pandemic - Johan G. Ony, Antonius Singgih Setiawan, Agustinus Widyartono, (Jurnal Akuntansi, 2021)
The COVID-19 pandemic, which has been around for more than a year, has changed habits in the world. The Covid-19 pandemic has also disrupted every aspect of global life such as business and trade and has had an impact on new behaviors and habits of business and economic activities. Another real impact of the Covid-19 pandemic is the risk of business survival. Therefore, the impact of the Covid-19 pandemic crisis must be a concern for entrepreneurs because it can disrupt business performance and business continuity. For this reason, this research was conducted to see whether the implementation of business strategies and the use of technology could have an impact on efforts to maintain the continuity of a business venture. The research data was collected by survey method to 200 respondents and 160 research data were collected (response rate 80%). Hypothesis testing is based on Structural Equation Modeling (SEM) Analysis of Partial Least Squares (PLS) using Warp PLS software version 5.0. The research findings conclude that the implementation of the strategy and the level of technology use has a positive impact on business continuity during the covid-19 pandemic.